2014
DOI: 10.1371/journal.pbio.1001792
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Effector HopX1 Targets JAZ Transcriptional Repressors to Activate Jasmonate Signaling and Promote Infection in Arabidopsis

Abstract: A bacterial effector protein, HopX1, targets host plant JAZ transcriptional repressors for degradation to activate the jasmonate pathway, thereby promoting bacterial pathogenesis by suppressing host defense responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
221
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(223 citation statements)
references
References 71 publications
2
221
0
Order By: Relevance
“…Another bacterial effector, HopX1 from P. syringae pv tabaci, degrades JAZs and thus promotes virulence by inhibiting SA defenses through activation of the JA pathway (Gimenez-Ibanez et al, 2014). Relatively little information is available on the molecular mechanisms of JA/SA cross talk, but it was recently found that COR induces the expression of NAC transcriptions factors that inhibit SA biosynthesis .…”
mentioning
confidence: 99%
“…Another bacterial effector, HopX1 from P. syringae pv tabaci, degrades JAZs and thus promotes virulence by inhibiting SA defenses through activation of the JA pathway (Gimenez-Ibanez et al, 2014). Relatively little information is available on the molecular mechanisms of JA/SA cross talk, but it was recently found that COR induces the expression of NAC transcriptions factors that inhibit SA biosynthesis .…”
mentioning
confidence: 99%
“…Because pathogenic organisms favor the use of secreted "effector" proteins to subvert host immunity, a great deal of research has focused on the role of pathogenic effectors and how they are used to modify the signaling of defense pathways controlled by plant hormones (10)(11)(12)(20)(21)(22)(23)(24). For example, the pathogenic bacteria Pseudomonas syringae and the oomycete Hyaloperonospora arabidopsidis secrete a number of effectors that target either JAZ proteins (10,11,23) or ethylene signaling (24), whereas Phytophthora infestans produces different effectors that interfere with SA-related signaling (21,22).…”
Section: Significancementioning
confidence: 99%
“…Because JAZ proteins are negative regulators of the JA signaling network, their degradation leads to transcriptional activation of plant defense networks within affected cells (6)(7)(8). Biotrophic pathogens have evolved methods of favoring JA signaling through the use of effector proteins because the outcomes of this hormonal pathway is considered less detrimental to their growth within plant tissues compared with defenses induced by other plant hormones [e.g., salicylic acid (SA)] (9)(10)(11)(12). Not all organisms attempting to colonize plant tissues, however, have adverse affects on plant health.…”
mentioning
confidence: 99%
“…Syringolin A, which is produced by some P. syringae pv syringae strains, acts as a proteasome inhibitor to open stomata and counteract stomatal innate immunity in bean (Phaseolus vulgaris) and Arabidopsis thaliana plants (Schellenberg et al, 2010). Furthermore, some the P. syringae effector proteins HopZ1a and HopX1 have recently been shown to assist bacterial entry through stomata (Jiang et al, 2013;Gimenez-Ibanez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis coi1 mutants do not respond to COR (Xie et al, 1998;Kloek et al, 2001) and do not support COR-induced stomatal opening and virulence (Mittal and Davis, 1995;Melotto et al, 2006). Similarly, HopZ1a acetylates and promotes the degradation of JAZ proteins, whereas HopX1 is a cysteine protease that directly degrades JAZ proteins, resulting in the activation of JA signaling and stomatal opening (Jiang et al, 2013;Gimenez-Ibanez et al, 2014). Recent findings indicate that JA signaling regulates stomatal opening through conserved NAM-ATAF-CUC2 (NAC) transcription factors, including ARABIDOPSIS NACs (ANAC019, ANAC055, and ANAC072) and tomato (Solanum lycopersicum) JA2-LIKE (JA2L) (Zheng et al, 2012;Du et al, 2014).…”
Section: Introductionmentioning
confidence: 99%